Strehl Ratio for Annular Eccentric Circular Aperture with Presence of Seidel Aberrations - Mohammed Faisal, Farah; Y. Hasan, Sundus (International Journal of Engineering and Technology, 2018)
In this research the equation of point spread function (PSF) has been derived for annular eccentric aperture optical system which is consisting of circular perture with non-central circular obscuration. The study was done with diffraction limited system and when different 1st and 3rd orders aberrations were present. Also trying to show how the presence of some 1st order errors with some of 3rd order aberrations were affected on Strehl ratio and make a balancing of aberrations which gives in turn a better image.Â Â